АНТИЖИТИЙНЫЕ МОТИВЫ ПОВЕСТИ НИКОЛАЯ ГОГОЛЯ ШИНЕЛЬ - Sklarow, Walerij (Przegląd Rusycystyczny, 2019)
MOTYWY ANTYHAGIOGRAFICZNE W POWIEŚCI NIKOŁAJA GOGOLA PŁASZCZ W artykule opierającym się na materiale powieści Nikołajа Gogola Płaszcz są sprawdzane o obecności w tym dziele hagiograficznych motywów i religijnego sensu. Przy analizie tekstu autor dochodzi do wniosku, że powieść nie posiada typowych cech charakterystycznych dla opisów żywotów świętych, co jest zgodne z popularną opinią innych badaczy tekstów Gogola, ale wręcz odwrotnie. Аutor dochodzi do wniosku, że Nikołaj Gogol wykorzystuje strukturę antyhagiografijną w celu budowania antytekstu i tworzenia innej kulturowej rzeczywistości — antyświata, który pomaga mu rozwiązać pewny literacki cel. THE OPPOSITE HAGIOGRAPHY IN THE NIKOLAI GOGOL’S STORY THE OVERCOAT In the article based on the Nikolai Gogol's The Overcoat are being verified the hypotheses about the actual presence of hagiographic motifs and a religious sense in the story. Author concludes that the story isn’t providing us with the typical genre based on the descriptions of a saint’s life as has been suggested by many researchers before, but is actually the opposite of the genre. This brings out the genre in Russian literature — «the anti-life». Exploring development of this genre in Russian literature, the author concludes that Gogol uses this structure in order to build and create a different cultural reality — «anti-world», which helps him to solve a certain literary goal.